Cadmium exposure promotes inflammation through the PPAR signaling pathway in the small intestine and colon of Hu sheep - Huimin Zhang; Shuo Yan; Ruilin Du; Yue Xue; Wenna Yao; Teligun; Yulong Zhao; Yongfa Li; Hanggai Bao; Shuo Cao; Xihe Li; Siqin Bao; et al. (Ecotoxicology and Environmental Safety)
With the increase of cadmium content in the environment, the losses caused by cadmium-induced intestinal diseases to animal husbandry are increasing year by year. However, most of the on-going research activities focus on zoonotic diseases rather than exploring the mechanisms of animal disease occurrence from an anthropogenic environmental perspective. In this study, stressed Hu sheep under cadmium environmental exposure were selected to explore the mechanism of inflammatory bowel disease development. 16 s, untargeted metabolomics and transcriptomic multiomics were used to analyze the changes of their intestinal tract and intestinal contents. The results showed that the beneficial microorganisms (s_Ruminococcus_sp) in the Cd group were significantly decreased and the potentially harmful microorganisms were significantly enriched, and the changes of these microorganisms affected the changes of metabolites (caprylic acid) to a certain extent, resulting in a decrease in fatty acids in the intestine. Due to the combined effect of cadmium ion and fatty acid reduction, the PPAR signaling pathway was inhibited, and the fatty acid transport and binding were further reduced, causing very serious damage to the intestine. We revealed for the first time the mechanism of intestinal injury in Hu sheeps under cadmium environmental exposure and provided new prevention and treatment methods of intestinal diseases under the environmental exposure to trace metals.